Eu-MOF and its mixed-matrix membranes as a fluorescent sensor for quantitative ratiometric pH and folic acid detection, and visible fingerprint identifying. Issue 22 (4th October 2021) - Jiang, Yansong; Huang, Yating; Shi, Xiangxiang; Lu, Zijing; Ren, Jiamo; Wang, Zimo; Xu, Jianing; Fan, Yong; Wang, Li
Abstract : The integration of 1 and polymer matrices leads to the fabrication of 1 @polymer MMMs, which can be used in the detection of pH and folic acid. Powder samples of 1 also show potential for application in fingerprint identification. Abstract : Here, we demonstrate the assembly of a new stable lanthanide-based metal–organic framework (MOF), Eu(HDPB)(phen) (1 ) (HDPB = (1, 1′:3′, 1′′-terphenyl)-3, 3′′, 5, 5′′-tetracarboxylic acid, phen = 1, 10-phenanthroline), with a three-dimensional framework under solvothermal conditions. 1 showed strong red fluorescence emission at room temperature and could be used as a selective and sensitive chemical sensor for pH and folic acid (FA) detection. Moreover, 1 could also be applied as a fluorescent material for the visible identification of fingerprints. Then, using 1 as a filler, two mixed-matrix membranes (MMMs), 1 @poly(ε-caprolactone) (PCL) and 1 @poly(vinylidene difluoride) (PVDF), have been fabricated. Notably, owing to the hydrophobic protection provided by the polymer matrix of the MOF particles, these two MMMs also exhibited fluorescence emission comparable to that of 1 and could be used for FA sensing with good selectivity and remarkable recyclability. More importantly, this is the first time that Eu-MOF-based MMMs have been employed in FA detection. The fabrication of MOF-based MMMs not only provides a facile method for sensing biomarkers, but it also enhances the recyclability of sensors.